Promosi Dakwah Badan Wakaf Indonesia dalam Mendistribusikan Produk Filantropi Islami untuk Pemberdayaan Ekonomi Umat - Yoga Agus Yulianto; Muhamad Zen; Fatmawati, Fatmawati (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study examines the role of the Indonesian Waqf Board (BWI) in promoting Islamic philanthropic da’wah, particularly through the distribution of waqf as a strategy for empowering the Muslim community’s economy in Indonesia. Waqf, as one of the core instruments of Islamic philanthropy, has substantial potential to reduce social inequality and improve community welfare. However, low public literacy about waqf, the lack of professionalism among waqf managers (nazhir), and limited use of digital technology remain key challenges. Using a qualitative approach through literature studies, observation, and document analysis, the study finds that BWI has implemented a transformative da’wah strategy by optimizing cross-sector collaboration, digital technology utilization, and community education. The results reveal that BWI's collaboration with Islamic financial institutions, government ministries, and civil society organizations has enhanced public engagement and the distribution of cash waqf, productive waqf, and waqf-based MSME programs. Moreover, the use of social media, mobile applications, and the waqf information system has expanded outreach and improved management transparency. This study concludes that the integration of da’wah, technology, and collaboration is essential in strengthening waqf as a viable tool for Islamic economic development. Moving forward, regulatory reform, comprehensive digitalization, and local community empowerment must become strategic priorities to sustain the national Islamic philanthropic ecosystem.